2000
DOI: 10.1038/sj.jp.7200330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Closed (Trach Care MAC) With an Open Endotracheal Suction System in Small Premature Infants

Abstract: OBJECTIVE:To determine whether ventilated, low birth weight infants treated with closed versus open tracheal suction in a neonatal intensive care unit (NICU) differ as to airway bacterial colonization, nosocomial pneumonia, bloodstream infection (BSI), incidence and severity of bronchopulmonary dysplasia (BPD), neonatal mortality, frequency of suction, reintubation, and nurse preference. STUDY DESIGN:A total of 175 low birth weight infants (Յ1250 gm) consecutively born (1997 to 1999), intubated, and ventilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
(19 reference statements)
1
36
0
8
Order By: Relevance
“…Although, the occurrence of VAP seems to be higher in multiple-use, open suction group, it did not meet the level of statistical significance. Our results are consistent with those findings of other researchers who reported that suctioning performed by closed-suction system does not increase the incidence of nosocomial pneumonia 10,12,22 . Even though, Combes et al argued that the incidence rate of VAP was lower for closed-suction system than open-suctioning, there was no follow up studies supporting their data 11 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although, the occurrence of VAP seems to be higher in multiple-use, open suction group, it did not meet the level of statistical significance. Our results are consistent with those findings of other researchers who reported that suctioning performed by closed-suction system does not increase the incidence of nosocomial pneumonia 10,12,22 . Even though, Combes et al argued that the incidence rate of VAP was lower for closed-suction system than open-suctioning, there was no follow up studies supporting their data 11 .…”
Section: Discussionsupporting
confidence: 93%
“…The reason for the increased colonization rate was explained by more frequent suctioning in the closed-suction system due to ease of the procedure. On the other hand, Cordero et al reported that closed suction group showed less colonization by Gram-negative bacilli compared to open suction group 10 . In the present study, the ratio of colonization by MRSA (colonization rate*100/number of discharged patient) was 8.86 for multiple-use, open suction group, 2.27 for single-use, open suction group and 4.94 for multiple-use, closed suction group.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another type of connector is the one that belongs to CSS devices, with sizes suitable for different sized ETTs. This system is advantageous in terms of maintaining tidal volume during aspiration and thus they are widely used in NICUs (7,8). Previously, Kazancı et al reported a 4%-16% increase in resistance with the use of CSS connectors when compared to standard connectors in their in vitro study (4).…”
Section: Discussionmentioning
confidence: 99%